ESTETIKA, RETORIKA, DAN IDEOLOGI PENGARANG DALAM NOVEL NIJUUSHI NO HITOMI (DUA BELAS PASANG MATA) KARYA SAKAI TSUBOI (KAJIAN STILISTIKA) - Novi andari; Khaira Imandiena Bahalwan (Universitas 17 Agustus 1945 Surabaya, 2016)
Sakai Tsuboi was one the Japanese writers who won rewards. One of his works Nijuushi noHitomi won a lot of appreciation from its readers. In this novel, Tsuboi showed his ideology of passivismor the love for peace and anti-war. The language of Nijuushi no Hitomi succeeded in attracting readers’attention, emotion, and thoughts. There were relationships among the dictions, language style, rethorics,and these relationships did not reduce the writer’s esthetical sense toward the sociohistorical events.Keywords : Estetika, Retorika, Ideologi Pengarang, Gaya Bahasa